Trophic ecology of the atlanto-iberian sardine (Sardina pilchardus) - Coelho, Carla Susana Ferreira Garrido (2007)
This dissertation aims at describing the trophic ecology of the Atlanto-Iberian sardine (Sardina pilchardus). Laboratory experiments studied the feeding behaviour of adult sardines while diet in the west (W) and south (S) Portuguese coast was examined through stomach and fatty acid (FA) analysis. Remote-sensed chlorophyll was compared to sardine diet. The ingestion of Pseudo-nitzschia was compared to the accumulation of domoic acid. The influence of diet on muscle composition and the maternal effects on the FA composition of the oocytes were studied. Sardines are highly omnivorous, using filter- and particulate-feeding depending of prey size and the most important prey were crustaceans (mainly eggs and copepods), fish eggs, dinoflagellates and diatoms. Feeding intensity matched satellite data being higher for the W. Sardines are vectors of domoic acid for predators, although no implications for human consumption are expected. The FA of sardine diet matched the dominance of phytoplankton in the diet for the W and carnivory for the S. Spatial differences of diet were reflected in the muscle, with higher EPA, EPA/DHA and (n-3)/(n-6) for the W. Seasonality of muscle FA composition was mainly driven by spawning. Female reserves influenced the FA composition of the oocytes, which might have implications for egg quality and ultimately, recruitment.